Pengaruh Kompetensi Manajerial Dan Sistem Pengendalian Internal Terhadap Kinerja Koperasi Simpan Pinjam Se - Kota Denpasar - Prabandari, I Gusti Agung Ayu Intan; Pramuki, Ni Made Wisni Arie; Ayu, Putu Cita (UNHI Press, 2025)
Cooperatives help the progress of society by providing loans to the community. One of the cooperatives, the artha guna werdhi cooperative, pemogan, did not implement standard operational procedures (sop) properly. Borrower budiarta said he borrowed idr 300 million and then increased it to idr 10 billion due to unclear calculations. However, budiarta was unable to pay it, so his credit went bad. The aim of this research is to determine whether management competence and internal control systems influence the performance of savings and loan cooperatives in denpasar city. In this research, 171 heads of savings and loan cooperatives in denpasar city were taken as samples. The sample determination was carried out using the probability sample method, and the analysis was carried out using partial least square (pls) analysis. The research results show that managerial competence has an insignificant positive influence on the performance of savings and loan cooperatives in denpasar city (h1 is rejected). Meanwhile, the internal control system has a significant positive effect on the performance of savings and loan cooperatives in denpasar city. This means that the second hypothesis in this research can be accepted (h2 is accepted). This research reminds that leaders of savings and loan cooperatives in denpasar city can improve their competence in leading cooperatives and related spi in ksp. It is hoped that they can be maintained and improved by paying attention to the control environment.